Ligation versus no ligation of spontaneous portosystemic shunts during liver transplantation: Audit of a prospective series of 66 consecutive patients. Issue 4 (26th March 2018) - Gomez Gavara, Concepcion; Bhangui, Prashant; Salloum, Chady; Osseis, Michael; Esposito, Francesco; Moussallem, Toufic; Lahat, Eylon; Fuentes, Liliana; Compagnon, Philippe; Ngongang, Norbert; Lim, Chetana; Azoulay, Daniel
Abstract : The management of large spontaneous portosystemic shunt (SPSS) during liver transplantation (LT) is a matter of debate. The aim of this study is to compare the short‐term and longterm outcomes of SPSS ligation versus nonligation during LT, when both options are available. From 2011 to 2017, 66 patients with SPSS underwent LT: 56 without and 10 with portal vein thrombosis (PVT), all of whom underwent successful thrombectomy and could have portoportal reconstruction. The SPSS were either splenorenal (n = 40; 60.6%), left gastric (n = 16; 24.2%), or mesenterico‐iliac (n = 10; 15.1%). Following portoportal anastomosis, the SPSS was ligated in 36 (54.4%) patients and left in place in 30 (45.5%) patients, based on the effect of the SPSS clamping/unclamping test on portal vein flow during the anhepatic phase. Intraoperatively, satisfactory portal flow was obtained in both groups. Primary nonfunction (PNF) and primary dysfunction (PDF) rates did not differ significantly between the 2 groups. Nonligation of SPSS was significantly associated with a higher rate of postoperative encephalopathy ( P  < 0.001) and major postoperative morbidity ( P  = 0.02). PVT occurred in 0 and 3 patients in the ligated and nonligated shunt group, respectively ( P  = 0.08). A composite end point, which included the relevant complications in the setting of SPSS in LT (ie, PNF and PDF, PVT, and encephalopathy) was present in 16 (44.4%) and 22 (73.3%) patients of the ligated and nonligated shunt group, respectively ( P  = 0.02). Patient ( P  = 0.05) and graft ( P  = 0.02) survival rates were better in the ligated shunt group. In conclusion, the present study supports routine ligation of large SPSS during LT whenever feasible. Liver Transplantation 24 505–515 2018 AASLD.